A porous rigid substrate, a method for preparing the same and a method for testing strength of two-dimensional materials

CN121825033BActive Publication Date: 2026-10-30QINGDAO UNIV OF TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511870826.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-12
Publication Date
2026-10-30
Estimated Expiration
2045-12-12

AI Technical Summary

Technical Problem

[0007]本发明的目的在于提供一种多孔刚性基底及其制备方法和二维材料强度的测试方法,以有助于解决或改善现有的石墨烯强度测试方法的工艺复杂、成本高、基底刚性不足、界面粘结困难和测试效率低中的至少一项的问题

Benefits of technology

本发明的石墨烯强度测试方法通过创新性地利用水性环氧树脂脱水成孔的自然特性构建多孔刚性基底,从根本上简化了传统方法中需要依赖电子束光刻、聚焦离子束刻蚀等昂贵微纳加工设备制备孔洞的复杂工艺,使多孔刚性基底的制备仅需常规的涂覆设备和加热设备即可完成;此外,制备周期从传统方法的数天至数周可缩短至数小时,单次制备成本从数千至数万元降低至数十元,成本降低了两个数量级以上,极大地提高了测试的可及性和经济性,使得普通实验室无需配置专业微纳加工平台即可开展石墨烯(或其他二维材料)的强度测试工作。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121825033B_ABST
    Figure CN121825033B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of two-dimensional material mechanical property testing, and particularly relates to a porous rigid substrate, a preparation method thereof and a two-dimensional material strength testing method. The preparation method of the porous rigid substrate comprises the following steps: step a, uniformly mixing an aqueous epoxy resin precursor and a curing agent solution to obtain an aqueous epoxy resin mixture, and determining and recording the water content in the mixture; the components of the aqueous epoxy resin precursor include an aqueous epoxy resin and water; step b, coating the aqueous epoxy resin mixture on the surface of a substrate; step c, pre-curing at 20-80 DEG C for 0.5-4 h; step d, heating to 80-150 DEG C for curing for 1-6 h; step e, cooling to room temperature, and the porous rigid epoxy resin substrate is obtained. The porous rigid substrate is suitable for mechanical property testing of two-dimensional materials, has a wide application prospect, and the preparation method is simple, efficient and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of two-dimensional material mechanical property testing technology, specifically relating to a porous rigid substrate and its preparation method, and a method for testing the strength of two-dimensional materials. Background Technology

[0002] Graphene, a two-dimensional carbon nanomaterial with a single atomic layer thickness, possesses extremely high theoretical strength (approximately 130 GPa), excellent electrical and thermal conductivity, good light transmittance, and a large specific surface area, demonstrating enormous application potential in flexible electronic devices, composite material reinforcement, sensors, energy storage, and biomedicine. The mechanical properties of graphene, especially its strength, are one of the key indicators determining its successful application in structural materials, flexible electronic devices, and functional coatings. Accurately testing the strength of graphene is of great significance for material quality control, process optimization, device reliability assessment, and promoting the industrialization of graphene.

[0003] However, graphene strength testing faces numerous technical challenges. Graphene is a single-atom-layer or few-layer structure with a thickness of only 0.335-3.35 nm, making it difficult to directly apply conventional material mechanics testing methods. Currently, graphene strength testing mainly relies on constructing a supporting substrate to suspend the graphene above pre-fabricated pores, and then determining its fracture strength by applying a load. The key to this testing method is: (1) preparing a supporting substrate with a regular microporous structure; (2) the substrate must have sufficient rigidity to avoid synergistic strain during testing; and (3) good interfacial adhesion is required between the graphene and the substrate.

[0004] Existing graphene strength testing methods mainly include: (1) Atomic force microscopy (AFM) nanoindentation method: Lee et al. (Science, 2008) first used AFM needle tip to pierce graphene suspended on pre-made holes and measured the intrinsic strength of monolayer graphene to be about 130 GPa. This method requires the pre-fabrication of micro-hole arrays on silicon substrates by means of electron beam lithography or focused ion beam etching. The process is complex, costly, and time-consuming. The cost of a single preparation can reach thousands to tens of thousands of yuan. In addition, it requires a professional micro-nano processing platform, which is difficult to realize in ordinary laboratories, which seriously restricts the promotion and application of this method. (2) Tensile test method: The graphene is directly clamped at both ends by a micro-nano operating system for tensile testing. However, the preparation and fixation of graphene samples are extremely difficult, and stress concentration is easily generated at the clamping point, which leads to premature sample failure. The test success rate is low, usually less than 30%. (3) MEMS device method: The test device with cantilever beam or thin film structure is prepared by using microelectromechanical systems and graphene is transferred onto the device for testing. However, the preparation of MEMS devices requires professional micro-nano processing equipment and clean room environment. The preparation cycle of a single device takes several weeks and the cost is extremely high, which limits the promotion and application of this method.

[0005] To address the aforementioned issues, there is an urgent need to develop a graphene strength testing method that is simple to prepare, low in cost, allows for precise control of pore size, provides suitable substrate rigidity, and exhibits strong interfacial adhesion.

[0006] Therefore, there is a need to provide an improved technical solution that addresses the shortcomings of the existing technology. Summary of the Invention

[0007] The purpose of this invention is to provide a porous rigid substrate and its preparation method, as well as a method for testing the strength of two-dimensional materials, so as to help solve or improve at least one of the problems of existing graphene strength testing methods, such as complex process, high cost, insufficient substrate rigidity, difficulty in interface bonding, and low testing efficiency.

[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a porous rigid substrate, comprising the following steps: Step a, mixing an aqueous epoxy resin precursor and a curing agent solution uniformly to obtain an aqueous epoxy resin mixture, and measuring and recording the water content in the mixture; the components of the aqueous epoxy resin precursor include aqueous epoxy resin and water; Step b, coating the aqueous epoxy resin mixture onto the surface of a substrate; Step c, pre-curing at 20-80℃ for 0.5-4h; Step d, heating to 80-150℃ and curing for 1-6h; Step e, cooling to room temperature to obtain the porous rigid epoxy resin substrate.

[0009] Preferably, in step a, the mass ratio of the waterborne epoxy resin precursor to the curing agent is 1:0.2-1:1.5.

[0010] Preferably, in step a, the water content in the mixture is 40wt%-50wt%.

[0011] Preferably, the components of the aqueous epoxy resin precursor further include rigid fillers and / or pore-forming agents; the rigid fillers are at least one of nano-silica, nano-alumina, carbon nanotubes and graphene oxide; the pore-forming agents are at least one of polyethylene glycol, polyvinylpyrrolidone, surfactants and inorganic salts.

[0012] Preferably, the amount of the rigid filler is 1wt%-20wt% of the mass of the waterborne epoxy resin, and the particle size of the rigid filler is smaller than the target pore size of the porous rigid substrate; the mass of the pore-forming regulator is 0.5wt%-10wt% of the waterborne epoxy resin.

[0013] Preferably, in step b, the coating thickness is 10-500 μm; the coating method is spin coating, blade coating or spray coating; in step d, the heating rate is 0.5-5℃ / min.

[0014] Preferably, in step d, the temperature is raised to 100-150℃ and cured for 3-6 hours; or, in step d, the micropore morphology is controlled by segmented drying temperature and time: in the first stage, the temperature is raised to 80-100℃ and dried for 1-3 hours; in the second stage, the temperature is raised to 100-150℃ and dried for 1-3 hours.

[0015] The present invention also provides a porous rigid substrate, which adopts the following technical solution: a porous rigid substrate, wherein the porous rigid substrate is prepared by the method described above.

[0016] Preferably, the surface micropores of the porous rigid substrate have a pore size of 0.5-50 μm, a pore depth of 0.1-20 μm, and a pore density of 10-10000 pores / mm². 2 .

[0017] Preferably, the porous rigid substrate has an elastic modulus ≥1 GPa and a surface roughness Ra ≤50 nm.

[0018] The present invention also provides a method for testing the strength of two-dimensional materials, which adopts the following technical solution: A method for testing the strength of two-dimensional materials includes the following steps: (1) Sample transfer: Transfer the sample film to the surface of the porous rigid substrate as described above, so that the sample is suspended above the micropores of the porous rigid substrate and bonded and fixed to the porous rigid substrate; (2) Strength test: Apply a load to the sample suspended above the micropores, record the force-displacement curve of the sample, and calculate the strength value of the sample; The sample is a two-dimensional material.

[0019] Preferably, in step (1), after the sample is transferred, the interfacial adhesion between the sample and the porous rigid substrate is enhanced by at least one of the following methods: (a) heat treatment at 50-120°C for 0.5-3 h; (b) applying a uniform pressure of 0.01-1 MPa for 0.5-2 h; (c) irradiating with ultraviolet light for 5-30 min; (d) coating the surface of the porous rigid substrate with a silane coupling agent or an adhesion promoter containing amino or carboxyl groups before the sample comes into contact with the porous rigid substrate.

[0020] Preferably, the two-dimensional material is at least one of graphene, molybdenum disulfide, tungsten diselenide, boron nitride, and black phosphorus; and the graphene is at least one of single-layer graphene, multilayer graphene, chemical vapor deposition graphene, graphene oxide, and reduced graphene oxide.

[0021] Beneficial effects: The graphene strength testing method of this invention innovatively utilizes the natural pore-forming properties of waterborne epoxy resin through dehydration to construct a porous rigid substrate. This fundamentally simplifies the complex process of preparing pores that traditional methods require expensive micro-nano processing equipment such as electron beam lithography and focused ion beam etching. The preparation of the porous rigid substrate can be completed using only conventional coating and heating equipment. In addition, the preparation cycle can be shortened from several days to several weeks in traditional methods to several hours, and the cost of a single preparation can be reduced from thousands to tens of thousands of yuan to tens of yuan, a cost reduction of more than two orders of magnitude. This greatly improves the accessibility and economy of testing, enabling ordinary laboratories to carry out strength testing of graphene (or other two-dimensional materials) without the need for a professional micro-nano processing platform.

[0022] This invention achieves micropores with varying pore sizes (0.5-50 μm), depths (0.1-20 μm), and densities (10-10000 pores / mm²) by controlling process parameters such as water content, drying rate, drying temperature, and degree of curing in waterborne epoxy resin. 2 The control of ) does not require the mask or expensive micro-nano processing equipment required by traditional methods.

[0023] This invention optimizes the amount of curing agent and curing conditions to achieve an elastic modulus of over 1 GPa for porous rigid substrates, which is more than two orders of magnitude higher than that of flexible substrates such as PDMS. This effectively avoids the problem of co-strain and improves the accuracy of testing.

[0024] This invention utilizes the π-π interaction and van der Waals forces between epoxy resin and graphene, combined with interface strengthening methods such as heat treatment and pressurization, to effectively avoid the slippage phenomenon of graphene during testing.

[0025] This invention is compatible with both puncture and pressure testing methods, making it widely applicable. The substrate preparation is simple, low-cost, and quick, and it is easy to mass-produce and standardize, providing reliable technical support for the quality control and performance evaluation of two-dimensional materials.

[0026] The porous rigid substrate of this invention is not only suitable for strength testing of different types of graphene materials (including monolayer graphene, multilayer graphene, chemical vapor deposition graphene, graphene oxide, and reduced graphene oxide), but can also be extended to the mechanical property characterization of other two-dimensional materials (such as molybdenum disulfide, tungsten diselenide, boron nitride, black phosphorus, etc.), and has broad application prospects. It has important application value in the fields of reliability assessment of flexible electronic devices, interfacial strength research of composite materials, and quality control of two-dimensional materials, and provides a simple, efficient, and low-cost testing solution for the basic research and industrial application of two-dimensional materials. Attached Figure Description

[0027] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein: Figure 1 The load-displacement curves of monolayer graphene under different porous rigid substrate conditions are shown.

[0028] Figure 2 This is an AFM plan view of the porous rigid substrate surface of Example 1.

[0029] Figure 3 This is an AFM three-dimensional topography image of the porous rigid substrate surface in Example 1.

[0030] Figure 4 This is an AFM planar image of the porous rigid substrate surface in Example 2, with a scanning area of ​​5.0 μm × 5.0 μm.

[0031] Figure 5 This is a schematic diagram of a two-dimensional material suspended above micropores in a porous rigid substrate (where "21" is the diameter of the micropore). Detailed Implementation

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.

[0033] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0034] In this invention, "suspension" refers to the following: when the sample film is laid on a porous rigid substrate surface, the sample film completely covers the microporous area of ​​the substrate surface. The edges of the sample film are tightly adhered to and bonded to the substrate surface surrounding the micropores, while the area of ​​the sample film directly above the micropores is free-floating due to the lack of support below. This suspended area of ​​the sample film can undergo independent elastic deformation under vertical loads, making it an effective testing area for strength testing.

[0035] This invention addresses at least one of the problems of existing graphene strength testing methods, such as complex processes, high costs, insufficient substrate rigidity, difficulty in interfacial bonding, and low testing efficiency, by providing a method for preparing a porous rigid substrate.

[0036] The inventors discovered that waterborne epoxy resin is an epoxy resin system containing a certain amount of water. During the curing and drying process, the water gradually evaporates, leaving a porous structure on the surface. This natural pore-forming characteristic provides a novel approach for constructing porous rigid substrates for testing. If the size of the surface microporous structure can be controlled, and the waterborne epoxy resin film can possess a certain rigidity to avoid synergistic strain with graphene, it is expected to be applied to the testing of graphene strength. This would allow for the development of a simple, low-cost, high-performance porous rigid substrate suitable for graphene strength testing.

[0037] The method for preparing a porous rigid substrate according to an embodiment of the present invention includes the following steps: Step a, mixing an aqueous epoxy resin precursor and a curing agent solution uniformly to obtain an aqueous epoxy resin mixture, and measuring and recording the water content in the mixture; the components of the aqueous epoxy resin precursor include aqueous epoxy resin; Step b, coating the aqueous epoxy resin mixture onto the surface of a substrate; Step c, heating at 20-80℃ (e.g., 20℃, 30℃, 40℃, 50℃, 60℃, 70℃ or... Pre-curing at 80°C for 0.5-4 hours (e.g., 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, or 4h); Step d: Curing at 80-150°C for 1-6 hours (e.g., 1h, 2h, 3h, 4h, 5h, or 6h); Step e: Cooling to room temperature to obtain a porous rigid epoxy resin substrate. In step c, the pre-curing step helps the waterborne epoxy resin form a preliminary cross-linked network, retaining most of the moisture. The main purpose of the pre-curing stage is to form a gel network of sufficient strength to maintain structural stability during subsequent drying, while retaining moisture to form micropores in the subsequent curing stage. In step d, the curing temperature and time together determine the degree of curing and cross-linking density of the epoxy resin, which in turn affects the rigidity of the porous rigid substrate. During the curing process, moisture gradually evaporates, forming a microporous structure on the surface of the coated film. In step d, the higher the curing temperature, the faster the moisture evaporates, and the finer the pore structure formed. The degree of curing of the waterborne epoxy resin can be adjusted by the amount of curing agent and the curing time. The higher the degree of curing, the greater the rigidity of the substrate when the pore structure is formed, and the more regular the pore morphology. If the curing temperature in step d is too low, the moisture evaporation rate is too slow, the epoxy resin is not fully cured, and the preparation cycle is long. The microporous structure formed at low temperatures is loose and has irregular edges, which will also affect the suspension quality of graphene. If the curing temperature is too high, it may cause the moisture to evaporate violently in a boiling manner, resulting in a severely uneven surface structure or even bubble defects. Excessively high temperatures may also cause the epoxy resin to over-cur, resulting in brittleness, microcracks may appear on the substrate surface, and high temperatures may cause the epoxy resin to decompose or discolor, affecting subsequent characterization and observation.

[0038] The method of the present invention can achieve the control of microporous structure and rigidity, and prepare a porous rigid substrate that can be used for graphene strength testing; in addition, the porous rigid substrate prepared by the method of the present invention also has good interfacial adhesion with graphene, and can be used for graphene strength testing.

[0039] In a preferred embodiment of the method for preparing the porous rigid substrate of the present invention, in step a, the mass ratio of the aqueous epoxy resin precursor to the curing agent solution is 1:0.2-1:1.5 (e.g., 1:0.2, 1:0.3, 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3, 1:1.5).

[0040] Preferably, the solid content of the waterborne epoxy resin (commercially available waterborne epoxy resin products are emulsions or dispersions with water as the dispersion medium) is 40wt%-60wt% (e.g., 40wt%, 45wt%, 50wt%, 55wt% or 60wt%), and the concentration of the curing agent solution (e.g., polyetheramine aqueous solution) is 50wt%-80wt% (e.g., 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%).

[0041] Preferably, in step a, the mass ratio of the aqueous epoxy resin precursor to the curing agent solution is 1:0.5-0.8 (e.g., 1:0.5, 1:0.6, 1:0.7, or 1:0.8). A higher curing agent content provides more active groups (such as amine groups), promoting more complete ring-opening and cross-linking of epoxy groups, forming a higher-density three-dimensional network structure, thereby significantly improving the rigidity and strength of the substrate. If the curing agent content is too low, the epoxy groups will not react completely, resulting in low cross-linking density, insufficient substrate rigidity, and difficulty in achieving an elastic modulus of 1 GPa. Unreacted epoxy groups may continue to react during subsequent use, leading to changes in substrate size and properties. If the curing agent content is too high, excessive curing agent will cause the curing reaction to be too fast, resulting in a sharp increase in system viscosity and affecting coating uniformity. Excessive curing agent may also cause excessive heat release during curing, generating thermal stress or even cracking. Furthermore, excessive residual curing agent will reduce the water resistance and chemical stability of the material.

[0042] In a preferred embodiment of the method for preparing the porous rigid substrate of the present invention, in step a, the water content of the aqueous epoxy resin mixture is 40wt%-50wt% (e.g., 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, or 50wt%). The water content of the aqueous epoxy resin mixture (which can be accurately determined by a Karl Fischer moisture analyzer or by drying and weighing) affects the pore size and pore density of the prepared porous rigid substrate; higher water content results in larger pore sizes and higher pore density. If the water content is too low, the number of pores formed is insufficient, and the pore size is too small (<0.5μm), making it difficult to meet the requirements of graphene suspension testing; furthermore, a low pore density limits the selectable testing area. If the water content is too high, excessive moisture will lead to violent evaporation during curing, resulting in unstable surface structure, interconnected pores forming cracks, and damage to the substrate integrity. Excessive moisture will also dilute the epoxy resin concentration, reducing the rigidity after curing, and the elastic modulus may be lower than 1GPa.

[0043] In a preferred embodiment of the method for preparing the porous rigid substrate of the present invention, the components of the aqueous epoxy resin precursor include a pore-forming agent, which is at least one selected from polyethylene glycol, polyvinylpyrrolidone, surfactant, and inorganic salt; the mass of the pore-forming agent is 0.5wt%-10wt% of the aqueous epoxy resin (e.g., 0.5wt%, 1wt%, 2wt%, 3wt%, 5wt%, 8wt%, or 10wt%). Polyethylene glycol, as a water-soluble polymer, evaporates or decomposes with water during the drying process, which can increase the pore size and improve the regularity of the pores; polyvinylpyrrolidone has good film-forming properties and can stabilize the pore wall structure during pore formation; the surfactant can reduce the water-epoxy interfacial tension and promote uniform pore formation; the inorganic salt (such as sodium chloride or potassium chloride) dissolves in water and evaporates with the water to form a crystal template, which can form pores of a specific size. The pore structure can then be obtained by washing away the salt with water. If the amount of pore-forming regulator added is too small (<0.5wt%), the effect on regulating the pore structure is not obvious; if the amount added is too large (>10wt%), it may affect the curing reaction of epoxy resin, reduce the mechanical properties of the substrate, and excessive pore-forming regulator residue may affect the interfacial bonding between the prepared porous rigid substrate and graphene.

[0044] In a preferred embodiment of the method for preparing the porous rigid substrate of the present invention, the components of the aqueous epoxy resin precursor further include a rigid filler; the rigid filler is at least one selected from nano-silica, nano-alumina, carbon nanotubes, and graphene oxide. The rigid filler helps to improve the modulus of the porous rigid substrate through a physical reinforcement mechanism, and the nanoscale filler can also generate strong interfacial interactions with the epoxy resin matrix, further enhancing the rigidity of the prepared porous rigid substrate. The selection of the rigid filler should consider its compatibility with the epoxy resin and its influence on micropore formation; nano-silica has excellent reinforcing effect and good dispersibility; nano-alumina provides higher modulus but is difficult to disperse; carbon nanotubes have ultra-high modulus and strength, but are costly and require surface modification to improve dispersion; graphene oxide has both reinforcing and interfacial adhesion improvement effects, but the amount added must be strictly controlled to avoid affecting transparency.

[0045] Preferably, the particle size of the rigid filler is smaller than the target pore size of the porous rigid substrate. This smaller pore size (i.e., the particle size of the rigid filler is smaller than the desired target pore size of the porous rigid substrate) helps prevent the rigid filler from clogging the micropores on the porous rigid substrate.

[0046] Preferably, the amount of rigid filler is 1wt%-20wt% of the mass of the waterborne epoxy resin (e.g., 1wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, or 20wt%). If the amount of rigid filler is too small (<1wt%), the reinforcing effect is not significant, and its contribution to improving the rigidity of the substrate is limited. If the amount of rigid filler is too large (>20wt%), the filler is prone to agglomeration, leading to uneven dispersion and potentially forming defects in the substrate, reducing mechanical properties. Excessive filler also significantly increases the viscosity of the system, affecting the coating process performance. Furthermore, high filler content may clog some micropores or alter the micropore formation mechanism, affecting the controllability of the pore structure.

[0047] Preferably, the waterborne epoxy resin is at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenolic epoxy resin, aliphatic epoxy resin and alicyclic epoxy resin.

[0048] Preferably, the curing agent solution is an aqueous solution or an aqueous emulsion of at least one of fatty amines, aromatic amines, polyether amines, polyamides and modified amines.

[0049] In a preferred embodiment of the method for preparing the porous rigid substrate of the present invention, in step b, the coating thickness is 10-500 μm (e.g., 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 300 μm, 400 μm, or 500 μm); the coating method is spin coating, blade coating, or spray coating. Spin coating is suitable for thin-layer preparation (10-100 μm), and the thickness can be precisely controlled by controlling the spin coating speed (1000-5000 rpm); blade coating is suitable for medium thickness (50-300 μm) using an adjustable-gap blade; spray coating is suitable for thicker coatings (200-500 μm) or large-area preparation.

[0050] Preferably, the substrate in step b is a silicon wafer, glass sheet, quartz sheet, mica sheet, or metal sheet; the surface roughness Ra of the substrate is ≤10nm.

[0051] Preferably, before step b, the process further includes coating the substrate surface with a silane coupling agent and curing it to form a coupling layer; the silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane. The coupling layer helps enhance the adhesion between the porous rigid substrate and the substrate (to help prevent the porous rigid substrate from detaching from the substrate surface during subsequent use), and is particularly suitable for substrates such as glass sheets and quartz sheets with weak adhesion to epoxy resin.

[0052] In a preferred embodiment of the method for preparing the porous rigid substrate of the present invention, in step d, the heating rate is 0.5-5℃ / min (e.g., 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, or 5℃ / min). The control of the heating rate significantly affects the micropore morphology; by controlling the heating rate, the rate of moisture evaporation can be adjusted; the faster the drying rate, the smaller the pore size and the shallower the pore depth. During rapid drying, surface moisture evaporates quickly, forming "sealed" pores that restrict further evaporation of inner moisture, resulting in shallow pores. Simultaneously, the high vapor pressure generated by rapid evaporation leads to numerous, albeit small, pores formed by breaking through the surface. If the heating rate is too fast (>5℃ / min), the rapid evaporation of surface moisture causes uneven surface structure, potentially resulting in surface cracks or defects and uneven pore size distribution, affecting test repeatability. Excessive moisture evaporation may also create stress within the substrate, causing warping and deformation. Conversely, if the heating rate is too slow (<0.5℃ / min), moisture evaporation is too slow, prolonging the preparation cycle and reducing production efficiency. Furthermore, at extremely slow evaporation rates, some moisture may be trapped in the cross-linked network during curing, forming closed pores rather than surface open pores, affecting the effectiveness of the microporous structure.

[0053] Preferably, in step d, the temperature is raised to 100-150℃ (e.g., 100℃, 110℃, 120℃, 130℃, 140℃, or 150℃) and cured for 3-6 hours (e.g., 3 hours, 4 hours, 5 hours, or 6 hours). The higher curing temperature not only helps to accelerate the curing reaction rate, but more importantly, it can activate epoxy groups that are difficult to react at room temperature, improving the final degree of curing. Simultaneously, the high temperature promotes the rearrangement and relaxation of molecular chain segments, eliminating internal stress and forming a more stable cross-linked network structure. A curing time of 3-6 hours helps to increase the cross-linking density; the extended curing time allows the epoxy groups in the epoxy resin system more time to react with the curing agent, while also promoting the further improvement of the already formed cross-linked network, reducing network defects, and improving cross-linking density and uniformity.

[0054] Preferably, the micropore morphology is controlled by segmented drying temperature and time: In the first stage, the temperature is raised to 80-100℃ (e.g., 80℃, 85℃, 90℃, 95℃, or 100℃) and dried for 1-3 hours (e.g., 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours), allowing surface moisture to slowly evaporate and form pores. In the second stage, the temperature is raised to 100-150℃ (e.g., 100℃, 110℃, 120℃, 130℃, 140℃, or 150℃) and dried for 1-3 hours (e.g., 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours), allowing inner layer moisture to evaporate and solidify, forming a microporous structure with controllable depth and size. Segmented control of drying temperature and time helps to more precisely control the pore structure; the first stage helps to allow surface moisture to slowly evaporate and form pores, while the second stage helps to allow inner layer moisture to evaporate and solidify, forming a microporous structure with controllable depth and size. This segmented process fully utilizes the differences in moisture evaporation rate and epoxy resin curing rate at different temperatures to achieve independent control of pore depth and pore size.

[0055] Preferably, in step d, the cooling rate when cooling to room temperature after curing is 1-10°C / min (e.g., 1°C / min, 3°C / min, 5°C / min, 7°C / min, 9°C / min, or 10°C / min). This cooling rate helps to avoid excessively rapid cooling that could cause thermal stress leading to substrate cracking or microporous structure deformation.

[0056] Preferably, after step d, the degree of curing of the waterborne epoxy resin is 60%-95% (e.g., 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%). Here, the degree of curing refers to the reaction conversion rate of the epoxy groups, which affects the density of the crosslinked network and the mechanical properties of the substrate. A higher degree of curing results in greater substrate rigidity and more regular pore morphology during pore structure formation. At higher degrees of curing, the epoxy resin network structure is more stable, better maintaining the pore shape and preventing pore collapse or deformation after moisture evaporation. If the degree of curing is too low (<60%), the epoxy resin crosslinking is insufficient, resulting in insufficient substrate strength and rigidity, with an elastic modulus potentially below 1 GPa, failing to effectively prevent synergistic strain. A substrate with low curing degree is prone to creep or deformation during subsequent graphene transfer and testing, affecting test accuracy. Furthermore, uncured epoxy groups may undergo unnecessary chemical reactions with graphene, affecting interfacial properties. If the curing degree is too high (>95%), the high cross-linking of epoxy resin will increase the brittleness of the material, and the substrate may crack during preparation or use. Excessive curing degree will cause the material to lose some flexibility and is prone to thermal stress cracking when the temperature changes. In addition, high curing degree may reduce the interfacial adhesion with graphene because the number of reactive active groups is reduced.

[0057] This invention proposes a porous rigid substrate, which is prepared by the method described above in the embodiments of this invention.

[0058] In a preferred embodiment of the porous rigid substrate of the present invention, the surface micropores of the porous rigid substrate have a pore size of 0.5-50 μm, a pore depth of 0.1-20 μm, and a pore density of 10-10000 pores / mm². 2 In practical applications, the formed microporous structure can be characterized using atomic force microscopy or scanning electron microscopy, and regions with uniform pore size and suitable pore depth can be selected for graphene strength testing.

[0059] Preferably, the porous rigid substrate has an elastic modulus ≥1 GPa and a surface roughness Ra ≤50 nm.

[0060] This invention also proposes a method for testing the strength of two-dimensional materials. The method for testing the strength of two-dimensional materials according to an embodiment of this invention includes the following steps: (1) Sample transfer: Transfer the sample film to the surface of the porous rigid substrate as described above, so that the sample is suspended over the micropores of the porous rigid substrate and bonded and fixed to the porous rigid substrate; (2) Strength test: Apply a load to the sample suspended over the micropores, record the force-displacement curve of the sample, and calculate the strength value of the sample; The sample is a two-dimensional material. Among them, "suspended" (corresponding to the English terms "suspended" or "free-standing") is a commonly used technical term in the field of mechanical testing of two-dimensional materials; In the pioneering paper on graphene strength testing published in this field, the expression "suspended graphene membranes over circular wells" is used to describe the same technical state; Specifically, refer to Figure 5 "Suspending the sample over the micropores of a porous rigid substrate" means that the sample film covers and spans the micropores, with the edge area of ​​the sample film bonded and fixed to the surface of the rigid substrate around the micropores, while the portion of the sample film directly above the micropores is in a free-floating state, forming a suspended film structure similar to a diaphragm.

[0061] In a preferred embodiment of the two-dimensional material strength testing method of the present invention, step (1) includes the following sample film transfer methods: (i) wet transfer method: transferring the sample grown or prepared on a support to the surface of a porous rigid substrate with the assistance of polymethyl methacrylate (PMMA); (ii) dry transfer method: directly transferring the sample to the surface of a porous rigid substrate with the assistance of a polydimethylsiloxane (PMMA) film; during the transfer process, ensuring that the sample is completely suspended above the micropores and that the edges are in full contact with the porous rigid substrate. For example, taking graphene samples, the wet transfer method involves transferring graphene grown or prepared on a support (such as copper foil, nickel foil, or silicon wafer) to the surface of a porous rigid substrate with the assistance of PMMA. The specific steps include: spin-coating PMMA (molecular weight approximately 950k, concentration 4wt%-8wt% chloroform solution) onto the graphene surface to form a support layer; removing the support using chemical etching methods (such as FeCl3 solution etching of copper foil or KOH solution etching of silicon wafers); transferring the graphene / PMMA film to deionized water for cleaning; using a porous rigid substrate to lift the graphene / PMMA film from the water surface, ensuring the graphene side contacts the substrate; and removing the PMMA after drying using acetone or chloroform. Wet transfer is suitable for transferring large areas of graphene, but care must be taken to ensure thorough cleaning as PMMA residue may affect interfacial adhesion. Dry transfer uses a polydimethylsiloxane (PDMS) film to assist in the direct transfer of graphene to the surface of a porous rigid substrate. The specific steps include: preparing a PDMS film (usually using Sylgard 184, with a base-to-curing agent mass ratio of 10:1), which cures to form a flexible, transparent film; attaching the PDMS film to the graphene surface, utilizing the van der Waals forces between PDMS and graphene for adsorption; and slowly peeling the PDMS off from the support graphite, where the graphene remains on the substrate due to its stronger adhesion to the epoxy resin substrate. Dry transfer avoids liquid environments and chemical reagents, resulting in a cleaner interface, but requires higher operational skills. During the transfer process, it is necessary to ensure that the graphene is completely suspended above the micropores, with its edges in full contact with the substrate. The position and state of the graphene can be observed in real time using an optical microscope, and the alignment can be adjusted as necessary. The effectiveness of the graphene suspension above the micropores can be confirmed by Raman spectroscopy; the G peak and 2D peak positions of the suspended graphene differ slightly from those of the supporting graphene, which can be used to determine the suspension quality.

[0062] In a preferred embodiment of the method for testing the strength of two-dimensional materials of the present invention, in step (1), after sample transfer, the interfacial adhesion between the sample and the porous rigid substrate is enhanced by one or a combination of the following methods to reduce sample slippage and strain loss during testing: (a) heat treatment at 50-120°C (e.g., 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C) for 0.5-3 hours (e.g., 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours); (b) Apply a uniform pressure of 0.01-1 MPa (e.g., 0.01 MPa, 0.05 MPa, 0.1 MPa, 0.2 MPa, 0.5 MPa, or 1 MPa) for 0.5-2 h (e.g., 0.5 h, 1 h, 1.5 h, or 2 h); (c) Irradiate with ultraviolet light for 5-30 min (to promote interfacial chemical bonding; e.g., 2 h, 2 h, 2 h, or 2 h); (d) Coat the substrate surface with a silane coupling agent or an amino- or carboxyl-containing adhesion promoter before the sample comes into contact with the substrate. The heat treatment in (a) helps promote the π-π stacking interaction between the sample (using graphene as an example) and the aromatic groups on the epoxy resin substrate surface, while simultaneously providing sufficient energy for the molecular chain segments at the interface to rearrange, eliminate interfacial voids, and increase the contact area. If the heat treatment temperature is too low (<50℃), the molecular thermal motion energy is insufficient, and the interface optimization effect is limited; if the heat treatment temperature is too high (>120℃), it may lead to increased thermal stress in graphene, resulting in wrinkles or partial desorption during cooling; excessively high temperatures may also change the surface properties of epoxy resin or cause the substrate to become over-cured and brittle. In (b), uniform pressure is applied to ensure that the graphene and the substrate surface are fully bonded; mechanical pressure is used to press the graphene against the porous rigid substrate surface, eliminating interfacial air, increasing the van der Waals contact area, and promoting the graphene to conform to the microstructure of the porous rigid substrate surface, forming a mechanical interlock. If the applied pressure is too low (<0.01MPa), the promoting effect on interfacial bonding is limited, and air gaps may exist between the graphene and the substrate; if the pressure is too high (>1MPa), it may damage the graphene structure, causing defects or cracks; excessive pressure may also cause the graphene to embed into the porous rigid substrate surface, affecting its suspension state and subsequent testing. In (c), the wavelength of ultraviolet light is 254-365 nm. Ultraviolet light irradiation helps promote interfacial chemical bonding. The energy of ultraviolet light can excite active groups on the surface of porous rigid substrates, promoting the formation of chemical bonds with graphene. Ultraviolet light can also generate ozone, introducing oxygen-containing functional groups on the surface of porous rigid substrates and graphene, enhancing interfacial interactions. If the irradiation time is too short (<5 min), the interfacial modification effect is not obvious; if the irradiation time is too long (>30 min), excessive ultraviolet irradiation may introduce too many defects into graphene, reducing its intrinsic strength; excessive ultraviolet irradiation may also lead to aging of the surface of porous rigid substrates.In (d), coating with a coupling agent or adhesion promoter involves coating the surface of the porous rigid substrate with a silane coupling agent or an amino- or carboxyl-containing adhesion promoter before the graphene comes into contact with the substrate. Silane coupling agents (such as γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane) can form a chemical bridge between the epoxy resin-based porous rigid substrate and the graphene. Amino-containing compounds (such as ethylenediamine and polyethyleneimine) can react with epoxy groups and bind to the graphene through hydrogen bonds. Carboxyl-containing compounds (such as acrylic acid and terephthalic acid) can enhance interfacial adhesion through hydrogen bonds and electrostatic interactions. The coating amount of silane coupling agent or adhesion promoter is typically 0.1-1 mg / cm². 2 (For example, 0.1 mg / cm) 2 0.3 mg / cm 2 0.5 mg / cm 2 0.8 mg / cm 2 or 1mg / cm 2 Applying too little coating will not produce noticeable results, while applying too much coating will create an excessively thick intermediate layer at the interface, which will actually reduce the bonding strength between the interfaces.

[0063] In a preferred embodiment of the method for testing the strength of two-dimensional materials of the present invention, in step (2), the load is applied by either a puncture method or a pressure method: the puncture method uses an atomic force microscope (AFM) or a nanoindenter, with a loading rate of 0.1-50 μN / s (e.g., 0.1 μN / s, 0.5 μN / s, 1 μN / s, 5 μN / s, 10 μN / s, 20 μN / s, 30 μN / s, 40 μN / s, or 50 μN / s) to apply the load to the porous rigid material. A vertical load is applied to the center of the sample on the micropores of the substrate until the sample breaks. The pressure method uses a microindenter or micro / nano mechanical testing system to apply a uniform or concentrated load to the sample suspended across the micropores of a porous rigid substrate at a loading rate of 0.1-100 mN / s (e.g., 0.1 mN / s, 0.5 mN / s, 1 mN / s, 5 mN / s, 10 mN / s, 20 mN / s, 50 mN / s, or 100 mN / s) until the sample breaks. AFM typically uses diamond-coated probes or high-hardness silicon probes with a tip radius of 20-50 nm and an elastic constant of 10-100 N / m. Load-displacement curves are continuously recorded during the test; a sudden drop in the curve occurs when the graphene breaks. The puncture method is suitable for nanoscale, high-precision testing and can accurately determine the intrinsic strength of single-layer or few-layer graphene with high spatial resolution, but the testing speed is slow, requiring several minutes to tens of minutes per test. The compressive method can apply a concentrated load using a spherical indenter (1-100 μm in diameter) or a uniformly distributed load using a planar indenter. The load-displacement curve is recorded during the test. The compressive method is suitable for micrometer-scale, large-area testing, and is relatively fast, with a single test completed in seconds to minutes, but its spatial resolution is lower than the puncture method. The choice of loading rate requires a trade-off between testing efficiency and accuracy. Slower loading rates (<1 μN / s for puncture, <1 mN / s for compressive) can more accurately capture the elastic deformation and fracture behavior of the sample (e.g., graphene), reducing the influence of dynamic effects, but the test time is longer. Faster loading rates can improve testing efficiency but may introduce inertial effects, leading to an overestimation of the measured fracture load. Generally, a loading rate of 1-10 μN / s is recommended for the puncture method and 1-10 mN / s for the compressive method.

[0064] Preferably, the calculation of sample strength requires selecting a suitable theoretical model based on the shape of the micropores. For circular micropores, thin film theory is used for calculation: Where σ is the strength of graphene (taking graphene as an example) (Pa or GPa), F is the fracture load (N), r is the radius of the circular micropore (m), and t is the thickness of graphene (m). This formula is based on stress analysis of axisymmetric films under a center-point load, assuming that the graphene is completely suspended, edge-supported, and that in-plane prestress is neglected. For square or rectangular micropores, plate theory is used for calculation: Where 'a' is the side length of the square micropore (m). This formula is based on the maximum stress of a simply supported thin plate under a load at its center point, and the coefficient 0.375 comes from the analytical solution of the elastic thin plate theory. Determination of graphene thickness: Single-layer graphene is usually taken as... (Graphene interlayer spacing), for multilayer graphene, it is calculated based on the number of layers n: The number of graphene layers can be determined using Raman spectroscopy (the intensity ratio of the G peak to the 2D peak) or AFM (height measurement). To improve the reliability of the test results, multiple tests should be performed, the average value should be calculated, and statistical analysis should be conducted to evaluate the reliability of the test results. It is generally recommended to perform at least 10 independent tests on the same sample, remove obvious outliers, and then calculate the average and standard deviation. The standard deviation reflects the repeatability of the test; the standard deviation / mean (coefficient of variation) should be less than 20% to be considered a reliable test result. If the coefficient of variation is too large, it is necessary to check whether there are problems in the substrate preparation, graphene transfer, and testing procedures.

[0065] The porous rigid substrate of the present invention, its preparation method, and the method for testing the strength of two-dimensional materials are described in detail below through specific embodiments.

[0066] The sources of the main raw materials used in the following examples are as follows: The waterborne epoxy resin precursor includes bisphenol A type epoxy resin waterborne emulsion (Nan Ya Epoxy Resin Co., Ltd., epoxy value 0.45-0.55 eq / 100g, solid content 40-60%); the waterborne curing agent includes polyetheramine aqueous solution (Huntsman Corporation, models D230 and D400, amine value 300-800 mg KOH / g); the rigid filler includes nano-silica (Cabot Corporation, CAB-O-SIL series, average particle size 10-50 nm, specific surface area 200-400 m²). 2 / g), nano-alumina (Xuancheng Jingrui New Materials Co., Ltd., average particle size 30-80nm, purity ≥99.9%), multi-walled carbon nanotubes (Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, diameter 10-30nm, length 1-10μm, purity ≥95%), graphene oxide (Ningbo RouCarbon Electronics Technology Co., Ltd., monolayer ratio ≥99%, sheet diameter 0.5-5μm); pore-forming regulators include polyethylene glycol (Sinopharm Chemical Reagent Co., Ltd., molecular weight 600, 1000); coupling agents and bonding promoters include γ-aminopropyltriethoxysilane (Dow Corning, purity ≥98%), γ-glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., purity ≥97%); substrates include monocrystalline silicon wafers (China Electronics Technology Group Corporation No. 46 Research Institute, crystal orientation... <100> Thickness 0.5mm, surface roughness Ra<5nm, glass slide (Corning, microscope slide grade); graphene includes chemical vapor deposition (CVD) graphene (Beijing Zhongke Liutan Technology Co., Ltd., monolayer graphene grown on copper foil).

[0067] Example 1 The method for preparing the porous rigid substrate in this embodiment includes the following steps: Step a: Weigh 50g of bisphenol A type epoxy resin aqueous emulsion (Nan Ya Epoxy Resin Co., Ltd., epoxy value 0.50eq / 100g, solid content 50%), add 25g of polyetheramine D400 aqueous solution (BASF, amine value 400mgKOH / g, aqueous solution concentration 70%), stir and mix evenly to obtain an aqueous epoxy resin mixture (water content 43.33wt%).

[0068] Step b: Place the monocrystalline silicon wafer (China Electronics Technology Group Corporation No. 46 Research Institute, crystal orientation) <100> The silicon wafer (with a thickness of 0.5 mm and a surface roughness Ra < 5 nm) was ultrasonically cleaned with acetone and isopropanol for 10 min in sequence, and then dried with nitrogen. The aqueous epoxy resin mixture was then coated onto the silicon wafer surface using a spin coating method at a spin coating speed of 3000 rpm and a spin coating time of 30 s to obtain a coating with a thickness of approximately 100 μm.

[0069] Step c: Place the coated silicon wafer in an oven and pre-cur it at 40°C for 2 hours.

[0070] Step d: Then heat to 120°C at a heating rate of 2°C / min, and cure at 120°C for 3 hours.

[0071] Step e: Control the cooling rate to 5℃ / min to reduce to room temperature, thus obtaining the porous rigid substrate of this embodiment; characterize the surface of the porous rigid substrate using atomic force microscopy (Bruker Dimension Icon, tapping mode). The scanning area is 50μm × 50μm (the AFM planar image of the porous rigid substrate surface of this embodiment is shown below). Figure 2 As shown, the AFM three-dimensional topography image is as follows: Figure 3 As shown in the figure (a three-dimensional perspective can clearly display the depth and morphological characteristics of the micropores), the results show that a uniformly distributed microporous structure is formed on the surface, with a pore size of 1.0-1.5 μm, a pore depth of 0.3-0.5 μm, and a pore density of approximately 2000 pores / mm². 2 The elastic modulus of the substrate was determined to be 2.8 GPa and the surface roughness Ra was 28 nm using a nanoindenter (Agilent G200).

[0072] The method for testing the strength of two-dimensional materials (CVD monolayer graphene in this embodiment) in this embodiment includes the following steps: (1) Graphene Transfer: CVD monolayer graphene (grown on copper foil by Beijing Zhongke Liutan Technology Co., Ltd.) was transferred to the surface of a porous rigid substrate using a wet method. Specific steps: PMMA (molecular weight 950k, 6wt% chloroform solution) was spin-coated onto the graphene surface and dried at 60℃ for 1 h; copper foil was etched with FeCl3 solution (0.5M) for 2 h; the graphene / PMMA was transferred to deionized water and washed three times; the graphene / PMMA was retrieved from the water surface using a porous rigid substrate; after drying at 80℃ for 30 min, PMMA was dissolved in acetone for 2 h, rinsed with isopropanol, and dried with nitrogen. The graphene was confirmed to be completely suspended above the micropores using an optical microscope.

[0073] (2) Interfacial bonding enhancement: The porous rigid substrate with transferred graphene was heat-treated at 80℃ for 1.5h to enhance interfacial bonding.

[0074] (3) Strength test: The test was conducted using the atomic force microscope (Bruker Dimension Icon) puncture method; a diamond-coated probe (Bruker DNISP, elastic constant 200 N / m, tip radius approximately 30 nm) was used for treatment. A microporous region with good graphene suspension was selected, and a vertical load was applied to the center of the suspended graphene at a loading rate of 5 μN / s until the graphene broke; the load-displacement curve was recorded, and the load dropped sharply when the graphene broke.

[0075] A micropore region with a pore size of approximately 1.0 μm (radius of approximately 0.5 μm) was selected for testing. Ten different micropores were tested, and the average fracture load was measured to be 189 ± 11 nN, corresponding to an indentation depth of approximately 25.0 nm (see...). Figure 1 (R0 curve). Since the substrate elastic modulus is 2.8 GPa, a synergistic strain effect exists. The strength is calculated using thin film theory. The strength is higher than that of graphene (approximately 130 GPa). The coefficient of variation for 10 tests was 6.0%, indicating good repeatability of the test results.

[0076] Example 1A The only difference between this embodiment and Embodiment 1 is that the aqueous epoxy resin mixture in step a also contains 2.5g of nano silica (the amount of nano silica is 5wt% of the bisphenol A type epoxy resin aqueous emulsion); the rest are consistent with Embodiment 1.

[0077] The elastic modulus of the porous rigid substrate in this embodiment was determined to be 3.5 GPa using a nanoindenter (Agilent G200). Strength testing was performed on micropores with a pore size of approximately 1.0 μm, and the average fracture load was measured to be 173 ± 9 nN, corresponding to an indentation depth of approximately 35.2 nm (see...). Figure 1 middle (Curve). The calculated apparent strength was 164 GPa, with a coefficient of variation of 5.5%.

[0078] Example 1B The only difference between this embodiment and Embodiment 1 is that the aqueous epoxy resin mixture in step a also contains 5g of nano silica (the amount of nano silica is 10wt% of the bisphenol A type epoxy resin aqueous emulsion); the rest are consistent with Embodiment 1.

[0079] The elastic modulus of the porous rigid substrate in this embodiment was determined to be 4.2 GPa using a nanoindenter (Agilent G200) (see [reference]). Figure 1 ).

[0080] Strength tests were conducted using micropores with a pore size of approximately 1.0 μm. The average fracture load was measured to be 157 ± 7 nN, corresponding to an indentation depth of approximately 48.6 nm (see...). Figure 1 middle (Curve). The calculated apparent intensity was 149 GPa, with a coefficient of variation of 5.0%.

[0081] Depend on Figure 1 It is known that the higher the substrate rigidity, the smaller the co-strain, and the greater the deformation required for graphene to reach its fracture strength, thus resulting in a greater indentation depth. However, since the actual strain across the suspended graphene is closer to the true value, the fracture load will differ slightly.

[0082] Example 2 The difference between the preparation method of the porous rigid substrate in this embodiment and that in Example 1 lies in the water content and curing conditions of the aqueous epoxy resin mixture. Specifically: in step a, 50g of bisphenol A type epoxy resin aqueous emulsion is weighed and 40g of polyetheramine D400 aqueous solution is added (the mass ratio of epoxy resin precursor to curing agent solution is 1:0.8), and the water content after mixing is 41.11wt%; in step b, a coating with a thickness of approximately 150μm is obtained by spin coating; in step c, pre-curing is performed at 60℃ for 1h; in step d, the temperature is increased to 100℃ at 3℃ / min, and then post-cured at 100℃ for 4h. The rest are consistent with Example 1.

[0083] The characterization results show (the AFM planar diagram of the porous rigid substrate surface in this embodiment is as follows) Figure 4 As shown, the porous rigid substrate of this embodiment has a micropore diameter of 1.5-2.5 μm, a pore depth of 0.4-0.6 μm, a pore density of approximately 1500 pores / mm², and an elastic modulus of 3.5 GPa. The porous rigid substrate of this embodiment was used for strength testing of graphene samples (same as in Example 1) using the same method.

[0084] Micropores with a pore size of approximately 2.0 μm (radius of approximately 1.0 μm) were selected for testing. The average fracture load was measured to be 276 ± 14 nN, and the graphene strength was calculated to be 131 GPa with a coefficient of variation of 5.2%.

[0085] Example 3 The difference between the preparation method of the porous rigid substrate in this embodiment and that in Example 1 lies in the water content and curing conditions of the aqueous epoxy resin mixture. Specifically, in step a, 50g of bisphenol A type epoxy resin aqueous emulsion is weighed, and 15g of polyetheramine D400 aqueous solution is added (the mass ratio of aqueous epoxy resin precursor to curing agent solution is approximately 1:0.3). Additionally, 2g of deionized water is added to make the water content of the mixture 45.32wt%. 2.5g of polyethylene glycol (PEG-600, Sinopharm Chemical Reagent Co., Ltd.) (5wt% of the bisphenol A type epoxy resin aqueous emulsion) is added as a pore-forming regulator, and the mixture is stirred evenly. In step b, a coating with a thickness of approximately 120μm is obtained by spin coating. In step c, pre-curing is performed at 30℃ for 3h. In step d, the temperature is increased to 110℃ at a rate of 1℃ / min, and then post-cured at 110℃ for 2h. All other steps are consistent with Example 1.

[0086] Characterization results show that the micropore size of the porous rigid substrate in this embodiment is 15-30 μm, the pore depth is 8-15 μm, and the pore density is approximately 200 pores / mm². 2 The elastic modulus of the substrate is 2.2 GPa.

[0087] Micropores with a pore size of approximately 20 μm were selected, and the porous rigid substrate of this embodiment was used for strength testing of graphene samples (same as in Example 1) in the same manner as in Example 1. The measured average fracture load was 2.94 ± 0.23 μN, and the calculated strength of graphene was 140 GPa with a coefficient of variation of 7.8%. Due to the low rigidity of the substrate (2.2 GPa), the synergistic strain effect resulted in an apparent strength slightly higher than the intrinsic value.

[0088] Example 4 The difference between the preparation method of the porous rigid substrate in this embodiment and that in Example 1 is as follows: In step a, 50g of bisphenol A type epoxy resin aqueous emulsion is weighed, and 28g of polyetheramine D400 aqueous solution is added. After mixing, the water content of the aqueous epoxy resin mixture is 39.06wt%. 7.5g of nano silica (Cabot Corporation, CAB-O-SIL M-5, average particle size 15nm; the mass of nano silica is 15wt% of the bisphenol A type epoxy resin aqueous emulsion) is added as a rigid filler. In the specific experiment, the nano silica is first ultrasonically dispersed in a small amount of bisphenol A type epoxy resin aqueous emulsion for 30min (frequency 40kHz, power 0.6W / cm). 3Then, the remaining bisphenol A type epoxy resin aqueous emulsion and polyetheramine D400 aqueous solution were added and stirred evenly; in step b, a coating with a thickness of about 100 μm was obtained by spin coating; in step c, it was pre-cured at 40°C for 2 h; in step d, the temperature was increased to 130°C at 2°C / min and then post-cured at 130°C for 4 h. The remaining steps were consistent with those in Example 1.

[0089] Characterization results show that the micropore size of the porous rigid substrate in this embodiment is 0.8-12 μm, the pore depth is 0.5-7 μm, and the pore density is approximately 600 pores / mm². 2 The elastic modulus of the substrate is 4.8 GPa.

[0090] The porous rigid substrate of this embodiment was used for strength testing of graphene samples (same as in Example 1) using the same method. A microporous region with a pore size of approximately 1.0 μm (radius of approximately 0.5 μm) was selected for testing, and the average fracture load was measured to be 141 ± 6 nN, corresponding to an indentation depth of approximately 65.0 nm (see...). Figure 1 middle (Curve). Strength calculated using thin film theory: The coefficient of variation is 4.5%. Due to the higher rigidity of the porous rigid substrate in this embodiment, the synergistic strain with the graphene sample is smaller during the test, and the measured strength value (134 GPa) is close to the intrinsic strength of graphene (about 130 GPa), and the coefficient of variation is lower, thus improving the accuracy and repeatability of the test.

[0091] Example 5 The difference between the preparation method of the porous rigid substrate in this embodiment and that in Example 1 is that: in step d, the temperature is increased to 90°C at 1.5°C / min, and then cured at 90°C for 2 hours (to allow the surface moisture to evaporate slowly and form pores); then the temperature is increased to 130°C, and cured at 130°C for 2 hours (to allow the inner layer moisture to evaporate and complete the curing); the remaining steps are consistent with those in Example 1.

[0092] Characterization results show that the microporous structure of the porous rigid substrate in this embodiment is more regular and uniform, with a pore size of 6-10 μm, a pore depth of 5-8 μm, and a pore density of approximately 1000 pores / mm². 2 The elastic modulus of the substrate is 3.2 GPa.

[0093] The porous rigid substrate of this embodiment was used for strength testing of graphene samples (same as in Example 1) using the same method as in Example 1. Micropores with a pore size of about 8.0 μm (radius of about 4.0 μm) were selected for testing. The average breaking load was measured to be 1.18 ± 0.06 μN, and the graphene strength was calculated to be 140 GPa with a coefficient of variation of 4.8%. The segmented curing process makes the microporous structure more regular, which is beneficial to improving the repeatability of the test.

[0094] Example 6 The difference between the preparation method of the porous rigid substrate in this embodiment and that in Example 1 is as follows: In step a, 50g of bisphenol A type epoxy resin aqueous emulsion is weighed, 25g of polyetheramine D400 aqueous solution is added, and 10g of deionized water is added. After mixing evenly, the water content of the resulting mixture is 50wt%; In step c, it is pre-cured at 50℃ for 3h; In step d, the temperature is increased to 115℃ at 2℃ / min and then cured for 3h; The rest are consistent with Example 1.

[0095] The porous rigid substrate prepared in this embodiment has micropores of 10-20 μm, a pore depth of 6-12 μm, and a pore density of 300 pores / mm². 2 The elastic modulus is 2.6 GPa.

[0096] The porous rigid substrate used in this embodiment was tested; the strength test was performed using the microindentation method (AntonPaarMCT3). A spherical diamond indenter (50 μm in diameter) was used to apply a load to the graphene suspended above the micropores with a diameter of approximately 15 μm at a loading rate of 5 mN / s until it fractured.

[0097] The average fracture load of the graphene (same as in Example 1) was measured to be 2.15 ± 0.18 μN, and the strength calculated using thin film theory was 136 GPa; the coefficient of variation for 10 tests was 8.2%.

[0098] Example 7 The porous rigid substrate of Example 1 was used for testing; the difference between the two-dimensional material (CVD bilayer graphene) strength test method in this example and Example 1 is that in step (1), CVD bilayer graphene (confirmed by Raman spectroscopy, the intensity ratio of 2D peak to G peak is about 1.6) was transferred to the surface of the porous rigid substrate by wet transfer (same as Example 1). Step (2) Interface strengthening treatment: heat treatment at 70°C for 2 hours and apply pressure of 0.2 MPa for 1 hour; the rest is consistent with Example 1.

[0099] The measured average fracture load was 255 ± 18 nN (pore size approximately 1.0 μm, radius approximately 0.5 μm), the thickness of the bilayer graphene was 0.67 nm, and the calculated strength was 121 GPa. The coefficient of variation was 7.1%.

[0100] Example 8 The difference between the preparation method of the porous rigid substrate in this embodiment and that in Example 1 is as follows: In step b, a glass slide (Corning, microscope slide grade) is used as the substrate. γ-aminopropyltriethoxysilane (Dow Corning, 2wt% ethanol solution) is first coated on the surface of the glass slide and cured at room temperature for 30 min to form a coupling layer as the substrate; then an aqueous epoxy resin mixture is coated (same as in Example 1); in step d, the temperature is increased to 120°C at 2°C / min and cured for 3 h; the rest is consistent with Example 1.

[0101] The porous rigid substrate prepared in this embodiment has micropores with a pore size of 5-15 μm and a pore density of approximately 500 pores / mm². 2 Its elastic modulus is 2.6 GPa.

[0102] The porous rigid substrate of this embodiment was used for testing; the difference between the testing method of the porous rigid two-dimensional material (the two-dimensional material in this embodiment is CVD monolayer graphene) in this embodiment and that in Example 1 is: in step (1), before the graphene transfer, γ-glycidyl etheroxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., 0.5 mg / cm³) is first coated on the surface of the porous rigid substrate. 2 The graphene was cured at room temperature for 1 hour, then cured at 80°C for 30 minutes. After that, the graphene was transferred to the surface of a porous rigid substrate treated with a coupling agent to enhance interfacial adhesion. The remaining steps were the same as in Example 1.

[0103] Micropores with a pore size of about 10 μm (radius of about 5 μm) were selected for testing. The average fracture load of the graphene (same as in Example 1) was measured to be 1430 ± 79 nN, and the strength was calculated to be 136 GPa with a coefficient of variation of 5.5%.

[0104] Example 9 The method for preparing the porous rigid substrate in this embodiment differs from that in Example 1 in the following ways: In step a, 50g of bisphenol A type epoxy resin aqueous emulsion is weighed and 50g of polyetheramine D400 aqueous solution is added (the mass ratio of curing agent to precursor is approximately 1:1), and the water content after mixing is 39.6wt%; 1g of carbon nanotubes (Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, surface modified by carboxylation, with an average diameter of 15nm; the amount of carbon nanotubes added is 2wt% of the mass of the bisphenol A type epoxy resin aqueous emulsion) are added and ultrasonically dispersed; in step b, a coating with a thickness of approximately 80μm is obtained by spin coating; in step c, pre-curing is performed at 70℃ for 1h; in step d, the temperature is increased to 150℃ at 4℃ / min and post-cured at 150℃ for 5h; the rest are consistent with Example 1.

[0105] Characterization results show that the porous rigid substrate of this embodiment has a small micropore size of 1-3 μm, a pore depth of 1-2 μm, and a pore density of approximately 2000 pores / mm².2 The base has an elastic modulus as high as 5.5 GPa.

[0106] Using the porous rigid substrate of this embodiment, the graphene strength was tested according to the same method as in Example 1; A specially designed ultrafine AFM probe (with a tip radius of approximately 10-15 nm, smaller than the 30 nm probe used in Example 1) was used for testing to accommodate the smaller micropore diameter in this example. Micropores with a diameter of approximately 1.0 μm (radius of approximately 0.5 μm) were selected for testing, and the average breaking load was measured to be 137 ± 8 nN. The graphene strength was calculated to be 130 GPa, with a coefficient of variation of 5.9%.

[0107] The porous rigid substrate in this embodiment has the highest rigidity (5.5 GPa) and the smallest synergistic strain effect. The measured strength value (130 GPa) is in high agreement with the intrinsic strength of graphene reported in the literature, which verifies the accuracy of the method of the present invention.

[0108] Example 10 The difference between the preparation method of the porous rigid substrate in this embodiment and that in Example 1 is as follows: In step a, 50g of bisphenol A type epoxy resin aqueous emulsion is weighed, and 12g of polyetheramine D400 aqueous solution is added (the mass ratio of epoxy resin precursor to curing agent solution is 1:0.24). In addition, 5g of deionized water and 4g of polyethylene glycol (PEG-1000; the amount of pore-forming regulator added is 8wt% of the bisphenol A type epoxy resin aqueous emulsion) are added to make the water content of the mixture reach 47.32wt%; In step b, a coating with a thickness of about 150μm is obtained by spin coating; In step c, it is pre-cured at 20℃ for 4h (a longer time to maintain the stability of the gel network); In step d, the temperature is slowly increased to 80℃ at a rate of 0.5℃ / min, and then post-cured at 80℃ for 6h.

[0109] Characterization results show that the micropore size of the porous rigid substrate in this embodiment is 30-45 μm, the pore depth is 15-18 μm, and the pore density is approximately 50 pores / mm². 2 The substrate has an elastic modulus of 1.5 GPa. This large-pore substrate is suitable for testing large-area graphene or for testing using the pressure method.

[0110] Using the porous rigid substrate of this embodiment, the strength of graphene was tested using a microindenter. A spherical indenter (100 μm in diameter) was used, and micropores with a diameter of approximately 35 μm were selected (the remaining test steps were the same as in Example 6). The average fracture load was measured to be 5.05 ± 0.48 μN, and the calculated graphene strength was 137 GPa with a coefficient of variation of 9.5%. Due to the low rigidity of the substrate, the synergistic strain effect resulted in a slightly higher apparent strength.

[0111] Comparative Example 1 The only difference between this comparative example and Example 1 is that the substrate was prepared using the conventional electron beam lithography method.

[0112] Specifically: A micro-hole array is prefabricated on a silicon wafer using electron beam lithography. A PMMA electron beam photoresist with a thickness of 200 nm is spin-coated onto the silicon wafer surface. A circular hole pattern with a diameter of 1 μm and a spacing of 20 μm is exposed on the photoresist using an electron beam exposure system (accelerating voltage 30 kV). After development, reactive ion etching (RIE) is used to etch the holes on the silicon wafer to a depth of approximately 300 nm. Residual photoresist is removed to obtain a substrate for graphene testing. The elastic modulus of the silicon substrate is approximately 165 GPa, which is much higher than that of the epoxy resin substrate of this invention, and can be considered a rigid substrate.

[0113] The graphene transfer and testing methods are the same as in Example 1.

[0114] Micropores with a pore size of 1.0 μm (radius of 0.5 μm) were selected for testing. The average fracture load was measured to be 137 ± 9 nN, and the graphene strength was calculated to be 130 GPa with a coefficient of variation of 6.5%.

[0115] The test results of this comparative example are consistent with those of Examples 4 and 9 (high-rigidity substrate), verifying that the intrinsic strength of graphene is approximately 130 GPa. However, substrate preparation requires specialized micro-nano processing equipment and a cleanroom environment, with a preparation cycle of up to 5 days and a single preparation cost of approximately 8,000 yuan, which is far higher than the method of this invention (preparation cycle of approximately 8 hours and cost of approximately 50 yuan).

[0116] Comparative Example 2 The only difference between this comparative example and Example 1 is that in step a, 50g of bisphenol A type epoxy resin aqueous emulsion was weighed and 60g of polyetheramine D400 aqueous solution was added (the mass ratio of epoxy resin precursor to curing agent solution is about 1:1.2), and the water content after mixing was only 39.09wt%; the rest were the same as in Example 1.

[0117] Characterization results show that the substrate prepared in this comparative example has a very small number of surface micropores, with a pore size of less than 0.5 μm and a pore density of only about 5 pores / mm. 2 Finding a suitable testing area is difficult. Although the substrate has a high elastic modulus of 6.2 GPa, the lack of appropriately sized micropores makes it impossible to effectively test the graphene strength. The comparative experimental results indicate that excessive curing agent can affect the pore-forming effect.

[0118] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step a, 50g of bisphenol A type epoxy resin aqueous emulsion was weighed, 10g of polyetheramine D400 aqueous solution was added, and 8g of deionized water was added to make the water content of the aqueous epoxy resin mixture reach 52.94wt%; the rest is consistent with Example 1.

[0119] In this comparative example, during the curing process, moisture evaporated rapidly, resulting in a severely uneven surface structure, multiple interconnected pores forming cracks, and damage to the integrity of the substrate. In some areas, the substrate peeled off from the silicon wafer.

[0120] The experimentally measured elastic modulus of the substrate in this comparative example was only 0.6 GPa (far below the 1 GPa requirement), which fails to meet the testing requirements. This indicates that excessive water content in the waterborne epoxy resin mixture can lead to substrate defects and insufficient rigidity.

[0121] Comparative Example 4 The only difference between this comparative example and Example 1 is that the amount of curing agent used is excessive. Specifically, in step a, 50g of bisphenol A type epoxy resin aqueous emulsion was weighed and 70g of polyetheramine D400 aqueous solution was added (the mass ratio of epoxy resin precursor to curing agent solution is 1:1.4), with a water content of 38.33wt%. The rest is consistent with Example 1.

[0122] During the coating process, it was found that the water-based epoxy resin mixture cured too quickly, gelling before spin coating, resulting in uneven coating thickness and noticeable flow marks and gel particles on the surface. After curing, the substrate surface was rough, with extremely uneven micropore distribution, and some areas of the substrate cracked. Although the elastic modulus of the substrate in this comparative example reached 7.5 GPa, the poor surface quality prevented effective graphene transfer and testing. This comparative example demonstrates that excessive curing agent solution leads to excessively fast curing, which negatively impacts substrate quality.

[0123] Comparative Example 5 The only difference between this comparative example and Example 1 is that the amount of curing agent used is too small. Specifically, in step a, 50g of bisphenol A type epoxy resin aqueous emulsion is weighed and 10g of polyetheramine D400 aqueous solution is added (the mass ratio of epoxy resin precursor to curing agent solution is 1:0.2), and the water content is 46.67wt%; the rest are consistent with Example 1.

[0124] The cured substrate surface was sticky and noticeably tacky to the touch, indicating incomplete curing. The measured elastic modulus of the substrate was only 0.5 GPa (below the 1 GPa requirement), and the degree of curing was only 38%.

[0125] After transferring graphene to the substrate, micropores with a pore size of approximately 1.0 μm were selected for testing. During the testing process, the substrate exhibited significant creep and severe synergistic strain with the graphene. The measured average fracture load was 425 ± 85 nN, and the calculated apparent strength was 404 GPa, which is much higher than the intrinsic strength of graphene. The coefficient of variation for 10 tests was as high as 20%, indicating poor repeatability.

[0126] The experimental results of this comparative example show that insufficient curing agent will lead to incomplete curing and insufficient rigidity of the substrate. The severe synergistic strain will result in a significantly higher measured apparent strength, which cannot accurately reflect the true strength of graphene.

[0127] Comparative Example 6 The only difference between this comparative example and Example 1 is that the drying rate is too fast; specifically, in step d, the temperature is rapidly increased to 120°C at a rate of 8°C / min, and then cured at 120°C for 3 hours; the rest are consistent with Example 1.

[0128] Due to the rapid temperature rise, the surface moisture evaporated quickly, resulting in multiple cracks and bubble defects on the substrate surface.

[0129] Characterization of the substrate in this comparative example revealed micropores ranging from 0.8 to 2.5 μm in size, with extremely uneven size distribution. Some areas showed interconnected pores forming cracks, and the pore density was approximately 1200 pores / mm². 2 The experimentally measured elastic modulus of the substrate in this comparative example was 2.5 GPa. Due to severe surface defects, the suspended mass of the transferred graphene was poor. Micropores with a pore size of approximately 1.0 μm were selected for testing, and the average fracture load was measured to be 152 ± 53 nN. The calculated graphene strength was 144 GPa, lower than that of Example 1 (2.8 GPa, 180 GPa), which had similar rigidity. This is because surface cracks and bubble defects caused the graphene to fracture prematurely at weak points, rather than through normal central penetration. The coefficient of variation reached 35%, indicating poor test reliability.

[0130] The comparative experimental results show that excessively fast drying rates can lead to surface structural defects, severely affecting test repeatability.

[0131] Comparative Example 7 The only difference between this comparative example and Example 1 is that the drying rate is too slow; specifically, in step d, the temperature is increased to 120°C at a rate of 0.2°C / min (taking about 7 hours), and then cured at 120°C for 3 hours; the rest is consistent with Example 1.

[0132] The total preparation time of the substrate in this comparative example exceeded 12 hours, resulting in extremely low production efficiency.

[0133] Although the obtained substrate microporous structure is relatively regular, with pore sizes of 1.0-1.8 μm, some moisture is trapped inside the cross-linked network during the extremely slow evaporation process, forming closed pores rather than surface open pores. The effective micropore density is only about 150 pores / mm² (far lower than the 2000 pores / mm² in Example 1), limiting the selectable testing area. The elastic modulus of the substrate in this comparative example is 2.5 GPa.

[0134] After graphene transfer, micropores with a pore size of approximately 1.0 μm were selected for testing. The average fracture load was measured to be 178 ± 12 nN, and the calculated graphene strength was 169 GPa with a coefficient of variation of 6.8%. This strength value is close to that of Example 1 (2.8 GPa, 180 GPa), which conforms to the physical law of co-strain (appearing strength is similar when the substrate rigidity is similar). Due to the lower substrate rigidity, there is a certain degree of co-strain, and the measured strength is slightly higher than the intrinsic value.

[0135] The experimental results of this comparative example show that a slow drying rate will prolong the preparation cycle and reduce the effective micropore density. Although the test results are acceptable, the production efficiency is low and it is not practical.

[0136] Comparative Example 8 The difference between this comparative example and Example 1 is that the curing temperature is too low; specifically, in step d, the temperature is increased to 70°C at a rate of 2°C / min, and cured at 70°C for 3 hours; the rest are consistent with Example 1.

[0137] After curing, the substrate surface softened, with an elastic modulus of only 0.7 GPa and a degree of curing of 55%. Moisture evaporation was insufficient, resulting in a loose microporous structure with irregular edges and a pore density of approximately 800 pores / mm². After graphene transfer, micropores with a pore size of approximately 1.0 μm were selected for testing. During the testing process, the substrate exhibited significant deformation, with an average fracture load of 298 ± 48 nN. The calculated apparent strength was 283 GPa, significantly higher than the intrinsic value, with a coefficient of variation of 16.2%.

[0138] The comparative experimental results show that: too low a curing temperature will lead to insufficient curing and insufficient substrate rigidity, and severe synergistic strain will lead to inaccurate test results.

[0139] Comparative Example 9 The difference between this comparative example and Example 1 is that the curing temperature is too high; specifically, in step d, the temperature is increased to 180°C at a rate of 2°C / min, and cured at 180°C for 3 hours.

[0140] During the curing process, moisture evaporates violently through boiling, resulting in numerous bubble defects and cracks on the surface. The substrate color darkens significantly to brown, indicating that the epoxy resin has undergone thermal degradation.

[0141] Although the elastic modulus of the substrate in this comparative example was as high as 8.2 GPa, the material became brittle, and multiple microcracks appeared in the substrate during graphene transfer, making effective testing impossible. The experimental results of this comparative example indicate that excessively high curing temperatures lead to resin degradation and substrate embrittlement.

[0142] Comparative Example 10 The difference between this comparative example and Example 1 is that no interface bonding strengthening treatment was performed; specifically, the preparation of the porous rigid substrate and the transfer of graphene are the same as in Example 1, but the interface strengthening step of 80°C heat treatment is omitted (step (2) is omitted), and the strength test is performed directly; the rest are consistent with Example 1.

[0143] During the testing process, it was found that graphene slipped significantly on the substrate surface when the AFM probe pierced it, and the load-displacement curve showed multiple irregular plateaus and jumps, indicating that the graphene was not firmly bonded to the substrate.

[0144] Micropores with a diameter of about 1.0 μm were selected for testing. The average fracture load measured in the experiment was only 120 ± 34 nN, and the calculated strength was 114 GPa, which was lower than 180 GPa in Example 1. The coefficient of variation of 10 tests was as high as 28%, indicating extremely poor repeatability.

[0145] The comparative experimental results demonstrate that interfacial bonding reinforcement is crucial for obtaining accurate and reliable test results. Without interfacial reinforcement, graphene slips under stress, failing to effectively transfer the load, resulting in lower measured fracture loads and strengths.

[0146] Comparative Example 11 The difference between this comparative example and Example 1 is that the amount of rigid filler added is excessive. Specifically, in step a, 50g of bisphenol A type epoxy resin aqueous emulsion was weighed, and 25g of polyetheramine D400 aqueous solution was added; 12g of nano silica was added (the amount of nano silica added is 24wt% of the bisphenol A type epoxy resin aqueous emulsion), and the water content of the aqueous epoxy resin mixture was 37.36wt%; the rest were consistent with Example 1.

[0147] Due to the excessively high content of rigid fillers in the waterborne epoxy resin mixture, the mixture has extremely high viscosity, making it difficult to disperse evenly and resulting in significant agglomeration. During spin coating, the coating thickness is severely uneven, and the surface is rough. After curing, observation revealed that a large number of rigid fillers blocked the micropores, drastically reducing the number of effective micropores to a pore density of only about 80 pores / mm². 2Although the experimentally measured elastic modulus of the substrate in this comparative example was as high as 9.5 GPa, due to the extremely limited usable test area and the agglomeration of rigid fillers forming defects, micropores with a pore size of approximately 1.0 μm were selected for testing. The average breaking load was measured to be 108 ± 45 nN, and the calculated graphene strength was 103 GPa, with a coefficient of variation of 42%, indicating large dispersion in the test results. The experimental results of this comparative example show that excessive addition of rigid fillers can lead to difficulties in dispersion, blockage of micropores, and affect the test quality.

[0148] Comparative Example 12 The difference between this comparative example and Example 1 is that a non-aqueous epoxy resin is used. Specifically, in step a, 50g of ordinary bisphenol A type epoxy resin (Nan Ya Epoxy Resin Co., Ltd., model E-51, epoxy value 0.51eq / 100g, pure epoxy resin without water) and 12g of polyetheramine D230 curing agent (industrial high-concentration product, water content <1%) are mixed to form an aqueous system; the rest is consistent with Example 1.

[0149] The epoxy resin substrate obtained after spin coating and curing has a smooth surface and is completely devoid of microporous structures. Therefore, it cannot be used for graphene suspension testing. To create pores, only expensive methods such as traditional electron beam lithography or focused ion beam etching can be employed.

[0150] Comparative Example 13 The difference between this comparative example and Example 1 is that PDMS is used as the substrate material. Specifically, PDMS (Sylgard 184, Dow Corning, base agent to curing agent mass ratio 10:1) is used to prepare the substrate. A micro-pillar array mold (pillar diameter 5μm, height 10μm, spacing 50μm) is imprinted on the PDMS surface, and a microporous array is formed after curing. All other aspects are consistent with Example 1.

[0151] CVD monolayer graphene was transferred onto the surface of a PDMS substrate. A puncture test was used with a loading rate of 5 μN / s. During the test, it was found that the elastic modulus of the PDMS substrate was only about 2 MPa (far below the required 1 GPa). When the AFM probe punctured the graphene, the PDMS substrate showed significant downward deformation, exhibiting severe synergistic strain with the graphene. Testing was conducted using micropores with a pore size of approximately 1.0 μm. The average breaking load was measured to be 485 ± 77 nN, and the calculated apparent strength was 461 GPa, significantly higher than the intrinsic strength of graphene, with a coefficient of variation of 15.8%.

[0152] The experimental results of this comparative example show that the synergistic strain caused by the severe lack of rigidity of the flexible substrate leads to a significantly higher measured apparent strength, which cannot accurately reflect the true strength of graphene, highlighting the importance of the high rigidity substrate of this invention.

[0153] Comparative Example 14 The difference between this comparative example and Example 1 is that the amount of pore-forming agent added is excessive. Specifically, in step a, 50g of bisphenol A type epoxy resin aqueous emulsion was weighed, and 25g of polyetheramine D400 aqueous solution was added; 8g of polyethylene glycol (PEG-600) was added as a pore-forming agent (the amount of polyethylene glycol added as a pore-forming agent was 16wt% of the bisphenol A type epoxy resin aqueous emulsion), and the water content of the aqueous epoxy resin mixture was 39.16wt%; the rest were consistent with Example 1.

[0154] After curing, the pore size of the substrate in this comparative example was measured to be 15-25 μm, the pore depth to be 8-12 μm, and the pore density to be 180 pores / mm². 2 The elastic modulus was only 0.9 GPa (below the 1 GPa requirement), indicating that excessive pore-forming agents affected the curing reaction of the epoxy resin and the formation of the cross-linking network; the surface roughness Ra of the substrate in this comparative example reached 85 nm.

[0155] After graphene transfer, micropores with a pore size of approximately 20 μm (radius of approximately 10 μm) were selected for testing. The average fracture load was measured to be 3520 ± 792 nN, and the calculated apparent strength was 167 GPa, with a coefficient of variation of 22.5%. Insufficient substrate rigidity led to synergistic strain, resulting in an overestimation of the strength. The experimental results of this comparative example indicate that the amount of pore-forming agent added needs to be strictly controlled.

[0156] In summary, the porous rigid substrates of Examples 1-10 of this invention all exhibit excellent performance, with an elastic modulus ≥1 GPa, meeting the rigidity requirements and effectively avoiding the problem of coordinated strain. The microporous structure dimensions are controllable, with pore diameters ranging from 0.5 to 50 μm, pore depths from 0.1 to 20 μm, and pore densities from 10 to 10,000 pores / mm². 2 Within this range, a suitable suspension platform can be provided for graphene strength testing. The measured graphene strength is in the range of 121-180 GPa, which is consistent with the intrinsic strength of graphene reported in the literature (approximately 130 GPa). The coefficient of variation is less than 10%, indicating that the test results are accurate, reliable, and have good repeatability.

[0157] This invention provides a graphene strength testing method that utilizes the natural pore-forming properties of waterborne epoxy resin during dehydration, enabling the preparation of simple and low-cost porous rigid substrates. By precisely controlling the water content, curing conditions, and drying process, the pore size, depth, and density of micropores can be accurately controlled to meet various testing requirements. Optimizing the amount of curing agent, curing temperature, and time, and adding an appropriate amount of rigid filler, a high-rigidity substrate with an elastic modulus ≥1 GPa can be obtained, effectively avoiding synergistic strain with graphene. Interfacial bonding strengthening treatment ensures a strong bond between graphene and the substrate, reducing slippage and strain loss. Compared to traditional methods, this invention shortens the substrate preparation cycle from several days to several hours, reduces costs by more than two orders of magnitude, simplifies the preparation process, eliminates the need for specialized micro / nano fabrication equipment and cleanroom environments, and can be easily implemented in ordinary laboratories. It enables standardized and batch testing, possessing significant research and application value. The method of this invention is not only applicable to the strength testing of single-layer and multi-layer graphene, but can also be extended to the mechanical property characterization of other two-dimensional materials (such as molybdenum disulfide, boron nitride, etc.), and has broad application prospects in the fields of quality control of two-dimensional materials, optimization of preparation process and reliability assessment of devices.

[0158] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a porous rigid substrate, characterized in that, Includes the following steps: Step a: Mix the waterborne epoxy resin precursor and the curing agent solution evenly to obtain a waterborne epoxy resin mixture, and measure and record the water content in the mixture; the components of the waterborne epoxy resin precursor include waterborne epoxy resin and water. Step b: Coat the substrate surface with the water-based epoxy resin mixture; Step c: Pre-cur at 20-80℃ for 0.5-4 hours; Step d: Heat to 80-150℃ and cure for 1-6 hours; the heating rate is 0.5-5℃ / min; after step d, the degree of curing of the waterborne epoxy resin is 60%-95%; Step e: Cool down to room temperature to obtain the porous rigid substrate; In step a, the mass ratio of the waterborne epoxy resin precursor to the curing agent is 1:0.2-1:1.5; in step a, the water content in the mixture is 40wt%-50wt%.

2. The method for preparing a porous rigid substrate as described in claim 1, characterized in that, The components of the waterborne epoxy resin precursor also include rigid fillers and / or pore-forming agents; The rigid filler is at least one of nano-silica, nano-alumina, carbon nanotubes, and graphene oxide. The pore-forming regulator is at least one of polyethylene glycol, polyvinylpyrrolidone, surfactant, and inorganic salt.

3. The method for preparing a porous rigid substrate as described in claim 2, characterized in that, The amount of the rigid filler is 1wt%-20wt% of the mass of the waterborne epoxy resin, and the particle size of the rigid filler is smaller than the target pore size of the porous rigid substrate; the mass of the pore-forming regulator is 0.5wt%-10wt% of the waterborne epoxy resin.

4. The method for preparing a porous rigid substrate as described in claim 1, characterized in that, In step b, the coating thickness is 10-500 μm; the coating method is spin coating, blade coating or spray coating.

5. The method for preparing a porous rigid substrate as described in claim 1, characterized in that, In step d, heat to 100-150℃ and cure for 3-6 hours; or, In step d, the micropore morphology is controlled by segmented drying temperature and time: the first stage is heated to 80-100℃ and dried for 1-3 hours; the second stage is heated to 100-150℃ and dried for 1-3 hours.

6. A porous rigid substrate, characterized in that, The porous rigid substrate is prepared by the method described in any one of claims 1-5.

7. The porous rigid substrate as described in claim 6, characterized in that, The porous rigid substrate has surface micropores with a pore size of 0.5-50 μm, a pore depth of 0.1-20 μm, and a pore density of 10-10000 pores / mm². 2 .

8. The porous rigid substrate as described in claim 7, characterized in that, The porous rigid substrate has an elastic modulus ≥1 GPa and a surface roughness Ra ≤50 nm.

9. A method for testing the strength of two-dimensional materials, characterized in that, Includes the following steps: (1) Sample transfer: The sample film is transferred to the surface of the porous rigid substrate as described in any one of claims 6-8, so that the sample is suspended over the micropores of the porous rigid substrate and bonded and fixed to the porous rigid substrate; (2) Strength test: Apply a load to the sample suspended above the micropore, record the force-displacement curve of the sample, and calculate the strength value of the sample; The sample is a two-dimensional material.

10. The method for testing the strength of two-dimensional materials as described in claim 9, characterized in that, In step (1), after sample transfer, the interfacial adhesion between the sample and the porous rigid substrate is enhanced by at least one of the following methods: (a) Heat treat at 50-120℃ for 0.5-3 hours; (b) Apply a uniformly distributed pressure of 0.01-1 MPa for 0.5-2 hours; (c) Irradiate with ultraviolet light for 5-30 minutes; (d) Before the sample comes into contact with the porous rigid substrate, a silane coupling agent or a bonding promoter containing amino or carboxyl groups is coated on the surface of the porous rigid substrate.

11. The method for testing the strength of two-dimensional materials as described in claim 9, characterized in that, The two-dimensional material is at least one of graphene, molybdenum disulfide, tungsten diselenide, boron nitride, and black phosphorus. The graphene is at least one of single-layer graphene, multilayer graphene, chemical vapor deposition graphene, graphene oxide, and reduced graphene oxide.

Citation Information

Patent Citations

  • Open-cell type heat-conducting epoxy matrix composite porous material and preparation method and application thereof

    CN104448713A

  • Method for preparing porous epoxy resin film

    CN105885071A